Rep protein of tomato yellow leaf curl geminivirus has an ATPase activity required for viral DNA replication. - Desbiez, C (1995)
The Rep protein of geminiviruses is the sole viral protein required for their DNA replication. The amino acid sequence of Rep protein contains an NTP binding consensus motif (P-loop). Here we show that purified Rep protein of tomato yellow leaf curl virus expressed in Escherichia coli exhibits an ATPase activity in vitro. Amino acid exchanges in the P-loop sequence of Rep causes a substantial decrease or loss of the ATPase activity. In vivo, mutant viruses carrying these Rep mutations do not replicate in plant cells. These results show that ATP binding by the Rep protein of geminiviruses is required for its function in viral DNA replication.